2001
DOI: 10.1002/ijc.1628
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a non‐functional p53 affects the sensitivity of cancer cells to gemcitabine

Abstract: Gemcitabine is a relatively new agent with promising activity in solid tumors. Few data are available regarding mechanisms of resistance to gemcitabine downstream from the drug-target interaction. The present study was performed to gain insight into the role of p53 status on the cytotoxicity of gemcitabine on cancer cells. Drug sensitivity, drug metabolism, cell kinetics and drug-induced apoptosis were compared in 2 lines derived from the mammary adenocarcinoma MCF-7: the wildtype p53 (wt-p53) containing MN-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 30 publications
4
59
0
Order By: Relevance
“…PancTu-1 cells showed only a moderate increase in apoptotic cell death under these conditions, whereas BxPc-3 and Capan-1 cells exhibited almost no induction of apoptosis. Cell cylce analysis revealed a gain of cells in G1/early S phase in all cell lines (data not shown), consistent with one of the actions of gemcitabine as an inhibtor of DNA elongation (Ng et al, 2000;Galmarini et al, 2002). This indicated that the uptake or intracellular targeting of gemcitabine was not altered in these cell lines, thus excluding a failure of drug uptake or of metabolism as being responsible for the resistance of these cell lines against gemcitabine.…”
Section: Discussionsupporting
confidence: 76%
“…PancTu-1 cells showed only a moderate increase in apoptotic cell death under these conditions, whereas BxPc-3 and Capan-1 cells exhibited almost no induction of apoptosis. Cell cylce analysis revealed a gain of cells in G1/early S phase in all cell lines (data not shown), consistent with one of the actions of gemcitabine as an inhibtor of DNA elongation (Ng et al, 2000;Galmarini et al, 2002). This indicated that the uptake or intracellular targeting of gemcitabine was not altered in these cell lines, thus excluding a failure of drug uptake or of metabolism as being responsible for the resistance of these cell lines against gemcitabine.…”
Section: Discussionsupporting
confidence: 76%
“…24,25 Similarly, MCF-7 cells and several pancreatic cancer cell lines expressing wt p53 were more susceptible to gemcitabine than the respective cell lines lacking active p53. 26,27 Although there are exceptions, each of the above studies is an example of a clear trend. However the role of p53 in etoposide-induced cytotoxicity is less clear, as some studies suggest a proapoptotic role for p53, especially in lymphoma and leukemia cells, 28,29 whereas other studies have concluded the opposite, for example with H1299 lung cancer cells.…”
Section: Role Of P53 In Chemotherapy Of Cervical Cancer Cellsmentioning
confidence: 99%
“…Another group comprises the genes involved in cell cycle regulation, proliferation, or apoptosis. Mutated p53 (13) and Bcl-xl (14,15) have been identified as possible molecular markers for gemcitabine chemoresistance, and both are directly involved in apoptosis. In addition, c-Src (16,17) and focal adhesion kinase (FAK; ref.…”
mentioning
confidence: 99%